2022
DOI: 10.1007/s11906-022-01191-8
|View full text |Cite
|
Sign up to set email alerts
|

Pet Ownership and the Risk of Arterial Hypertension and Cardiovascular Disease

Abstract: Purpose of Review Hypertension prevention and cardiovascular risk reduction are cornerstones in the prevention and treatment of cardiovascular diseases. Potential applicability of nontraditional cardiovascular risk reduction methods, such as pet ownership, raises a growing interest. Recent Findings Studies show that having pets may reduce the risk of death from any cause, particularly from cardiovascular causes. Furthermore, results of some studies indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Because the prevalence of allergic diseases is on the rise in developing countries and poses a signi cant socio-economic burden, whether pet exposure increases the risk of allergic diseases has become a focus of debate in the scienti c community [15]. Additionally, relationships between pet exposure and mortality remain inconclusive, with inconsistent ndings from prospective studies [9][10][11][12][13][14]. Potential reasons for the discrepancies include varied study designs, sample sizes, and insu cient consideration of differences between pet species .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the prevalence of allergic diseases is on the rise in developing countries and poses a signi cant socio-economic burden, whether pet exposure increases the risk of allergic diseases has become a focus of debate in the scienti c community [15]. Additionally, relationships between pet exposure and mortality remain inconclusive, with inconsistent ndings from prospective studies [9][10][11][12][13][14]. Potential reasons for the discrepancies include varied study designs, sample sizes, and insu cient consideration of differences between pet species .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the relationship between pet exposure and mortality also remains controversial. Some prospective cohort studies showed no association between dog or cat ownership and all-cause mortality [9][10][11], whereas other studies demonstrated pet keeping could reduce all-cause mortality risk [12][13][14]. Potential reasons for these inconsistent conclusions could be small sample sizes, study design differences, and insu cient consideration of differential impacts of pet species.…”
Section: Introductionmentioning
confidence: 99%
“…Our study also assessed factors that are not regarded as increasing hypertension risk, e.g., having home pets, consuming 2-3 cups of black coffee daily, vitamin D deficiency and female gender [19,36,61,62]. Although a large percentage of respondents had no knowledge of these factors, almost 1/5 of respondents stated that having home pets increases the risk of hypertension, and nearly 60% expressed the incorrect belief that coffee increases BP.…”
Section: Discussionmentioning
confidence: 99%
“…5 Further, previous studies highlighted how having a pet, mainly a dog, might facilitate the adoption of a healthier lifestyle that is primarily characterized by higher levels of physical activity, thus decreasing cardiovascular risk factors. 6 The present study is a pilot observational case-control study that aimed to investigate whether owning a companion animal might influence lifestyle habits and the perception of disease activity in a cohort of patients with RA.This study included 100 adults (aged ≥ 18 years) with established RA 7-9 : 50 patients who owned at least 1 companion animal (case group), and a sample of 50 patients with RA with no pets (control group) matched for age, sex, and disease duration (± 5 yrs). Patients with overlap syndromes were excluded.…”
mentioning
confidence: 99%
“…5 Further, previous studies highlighted how having a pet, mainly a dog, might facilitate the adoption of a healthier lifestyle that is primarily characterized by higher levels of physical activity, thus decreasing cardiovascular risk factors. 6 The present study is a pilot observational case-control study that aimed to investigate whether owning a companion animal might influence lifestyle habits and the perception of disease activity in a cohort of patients with RA.…”
mentioning
confidence: 99%